2020
DOI: 10.1021/acsami.0c06186
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Bmi1 by Ubiquitination and Proteasomal Degradation Inhibit Bcl-2 in Acute Myeloid Leukemia

Abstract: Bmi1 is associated with advanced prognosis of acute myeloid leukemia (AML), and polyethylenimine (PEI)-stabilized Bmi1 siRNA-entrapped human serum albumin (HSA) nanocarriers (PEI@HSANCs) were used to protect siRNA from degradation and also to control epigenetic regulation-based AML therapy. The nanoform increased the transfection efficiency of Bmi1 siRNA through caveolae-mediated endocytosis and enhanced Bax translocation into the mitochondria. It enhanced the caspase 3-mediated apoptosis through the Bax activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…This ICG-tagged stable nanosized complex not only allowed the visualization of the expression of EZH2 in the engrafted tumor in a leukemia mouse model but also could inhibit tumor growth by targeting EZH2. Some other studies have also confirmed the feasibility of epigenetic regulation-based strategies for precision treatment of cancer (Dev et al 2021;Kushwaha et al 2020;Sardoiwala et al 2020).…”
Section: Histone Methylationmentioning
confidence: 77%
“…This ICG-tagged stable nanosized complex not only allowed the visualization of the expression of EZH2 in the engrafted tumor in a leukemia mouse model but also could inhibit tumor growth by targeting EZH2. Some other studies have also confirmed the feasibility of epigenetic regulation-based strategies for precision treatment of cancer (Dev et al 2021;Kushwaha et al 2020;Sardoiwala et al 2020).…”
Section: Histone Methylationmentioning
confidence: 77%
“…The drug uses PEI and has as nanocarriers and encapsulates si-Bmi1 for Bmi1 gene. In animal experiments, this nanomedicine substantially prolonged the survival of diseased mice [ 235 ]. Similarly, Chandran et al .…”
Section: Nanomedicine Strategies Against Hmsmentioning
confidence: 99%
“…Some studies have shown that the polycomb protein Bmi1 is overexpressed in AML and plays a role in disease development through its downstream targets [ 74 ], making it a potential epigenetic target. Kushwaha et al proposed a delivery strategy using HSA nanoparticles as carriers (nanocarriers, NCs) for Bmi1 siRNA, which was stabilized by polyethylenimine (PEI) [ 61 ]. This innovative approach, known as PEI@HSANCs, aimed to enhance the effectiveness of Bmi1 siRNA delivery.…”
Section: Hsa-based Multifunctional Nanocarriermentioning
confidence: 99%
“… Schematic representation of the construction of HSA NPs-PEI@EZH2 siRNA and the possible mechanism of AML therapy. Reproduced with permission from the work of Kushwaha et al (2020) [ 61 ]. …”
Section: Figurementioning
confidence: 99%